Dependence of Vapor Compression in Cavitation Bubbles in Water and Benzol on Liquid Pressure - A.A. Aganin; M.A. Ilgamov; D.Yu. Toporkov (Учёные записки Казанского университета: Серия Физико-математические науки, 2016)
The features of strong vapor compression inside cavitation bubbles in benzol during their collapse have been studied depending on the liquid pressure in the range from 0.15 through 15 bar (the liquid temperature is 20 °C, the initial radius of the bubble is 500 μm). It has been found that three scenarios are implemented in this range of the liquid pressure: nearly homogeneous compression, compression by the radially converging simple waves, and compression by the radially converging shock waves. Shock waves are formed inside the bubble when the liquid pressure exceeds 0.25 bar. In contrast to benzol, there is only one possible scenario implemented in the case of cavitation bubble collapse in water under the same conditions, i.e., nearly homogeneous compression.